Personality and preventive healthcare utilisation: Evidence from the Irish Longitudinal Study on Ageing. - Mc Crory, Cathal (My University, 2019)
There is extensive empirical evidence that personality is associated with many outcomes and behaviours, such as educational outcomes, labour market participation, savings behaviour, health behaviours, physical health status and mortality. Use of preventive healthcare services (e.g., vaccinations, screening, etc.) is a potential pathway explaining the link between personality and health, and is an important component of healthy ageing. We examine the association between personality traits (the ‘Big Five’) and a variety of preventive healthcare uti- lisation measures in the older population. Using data from the Irish Longitudinal Study on Ageing (TILDA), we estimate Poisson models of preventive healthcare utilisation (influenza vaccination, blood cholesterol test, breast lump check, mammogram, prostate examination, prostate-specific antigen (PSA) test). We find that openness to experience is a significant predictor of breast lump check and mammogram in women aged 65+ after adjust- ment for other confounders and multiple hypothesis testing. While uptake of many preventive healthcare ser- vices remains below national recommendations for the older population, with the exception of breast lump checks and mammograms for women aged 65+, we find little evidence to link this heterogeneity in uptake to personality.
PUBLISHED
Keywords: Preventive healthcare; Personality; Older population; Ireland; Ageing; Healthcare Utilisation; PERSONALITY; Health